The role of human resource management in enterprise management Take scenic spot as an example - DR. XIAOJUN WANG; DR. ALBATTAT AHMAD; TONGQIAN ZOU (International Journal of Multidisciplinary Research and Studies, 2024)
This study delves into the significance of human resource management in scenic area management. As an integral part of the tourism industry, the management and operation of scenic areas heavily rely on human resources. The study first introduces the concepts and backgrounds of scenic area management and human resource management, laying the groundwork for a profound analysis of the pivotal role of human resource management in the management of scenic areas. We emphasize the analysis of how human resource management influences the operational efficiency and customer satisfaction of scenic areas, playing an essential and vibrant role. Next, this paper discusses the challenges faced in implementing human resource management in scenic areas. Deep analysis is given to the existent human resource strategies, and countermeasures are proposed based on the actual environment. By evaluating and optimizing the strategies and practices of human resource management, its role in scenic area management is further enhanced. We then explore and showcase through case studies how scenic areas, which have successfully implemented human resource management strategies, manage to retain employees, and significantly improve operational efficiency. The conclusion elucidates the central position of human resource management in scenic area management. It not only affects the operational efficiency of scenic areas but also directly touches on the satisfaction and return rate of tourists. Therefore, only by paying full attention to and optimizing the human resource management of scenic areas can we truly realize optimal management and effectively enhance the operational effects of scenic areas. Future research directions should continue to unearth the potential of human resource management in the tourism industry and in-depth scenic area management, so as to promote its practical application and in-depth theoretical research.